MEMODELKAN DAMPAK DAN KEBERLANJUTAN PARIWISATA PESISIR DI KABUPATEN BADUNG – PROVINSI BALI - DWIPAYANA, NGURAH P.; KENCANA, EKA N.; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika; Vol 7 No 2 (2018), 2018)
Tourism has been positioned as rising industry since year 2000s. Despite of its position as the primary mover for economic development and increasing the welfare of local people at the destination, tourism also induces some negative impacts regarding the social as well environment dimension for the destination and its surrounding. This essay is directed to study the impacts of marine tourism that take places at coastal region of Badung regency of Bali province. Utilising proportionally random sampling, 180 local people at District of Mengwi at Badung were selected as the sample's members for the study. Three dimensions of tourism sustainability i.e. economic, socio-cultural, and environment dimension were positioned as the exogenous latents while tourism impact was perceived by the local is placed as the endogenous one. In additon, this impact is hypothesed a ects the sustainability of marine tourism at this district. A covariance-based structural equation model was built to elaborate the causal relationship among these latent variables. Our research confirmed all of exogenous latents significantly affect people perception about tourism impact with socio-cultural dimension dominates the others' impact, and in turn, this impact - from supply perspective - affects marine tourism sustainability at Mengwi district of Badung regency.